(15)O-H(2)O PET/CT as a tool for the quantitative assessment of early post-radiotherapy changes of heart perfusion in breast carcinoma patients - Żyromska, Agnieszka (Br J Radiol, 2018)
OBJECTIVE: Studies examining radiation-induced heart toxicity in breast cancer patients are inconclusive. The aim of this study was to prospectively and quantitatively asses myocardial blood flow (MBF) with, for the first time, (15)O-H(2)O PET/CT as a marker of heart damage in irradiated breast cancer patients. METHODS: 15 breast cancer patients receiving intact breast or chest wall irradiation were included in the analysis (six with right-sided and nine with left-sided breast cancer). They underwent (15)O-H(2)O PET/CT before radiotherapy (RT) and 2 and 8 months after RT. MBF was quantitatively assessed at rest and under stress conditions in 17 heart segments distinguished according to the American Ultrasound Association classification. Regional MBF values were derived in each of the coronary artery territories. RESULTS: MBF decreased in 53% and increased in 33% of cases 2 months after RT in both left-sided and right-sided breast cancer patients. Stress testing was more sensitive than at-rest testing, demonstrating decreased perfusion in the segments supplied by the left anterior descending coronary artery (LAD) [5.41 ± 1.74 vs 4.52 ± 1.82 ml (g*min)(−1); p = 0.018], which persisted at 6 months [5.41 ± 1.74 vs 4.40 ± 1.38 ml (g*min)(−1); p = 0.032] and a decrease in global heart perfusion [5.14 ± 1.49 vs 4.46 ± 1.73 ml (g*min)(−1); p = 0.036]. A minimal radiation dose applied to the LAD correlated with MBF changes observed 2 months after RT (r = −0.57; p = 0.032). Radiological findings were not correlated with clinical symptoms of heart toxicity. CONCLUSION: (15)O-H(2)O PET/CT is safe and effective for the early detection and quantitative analysis of subclinical post-RT changes in heart perfusion in breast cancer patients. The LV segments supplied by the LAD are the main site of MBF changes. A minimum radiation dose deposited in the LAD may be a predictor of radiation-induced heart toxicity. ADVANCES IN KNOWLEDGE: This is the first time that (15)O-H(2)O PET/CT has been used to assess MBF after RT and the first granular description of the distribution of blood flow changes after breast cancer RT.